The Impact of International Trade on Economic Growth: A Case Study of Pakistan - Ghaffar, Suleman; Munir, Humaira; Nawaz, Shahbaz; Javaid, Anam (Asian Journal of Social Sciences and Management Studies, 2019)
International trade has its importance in economic growth of a country. Country that is good in international trade means that it is stable in its economic conditions. International trade also shows the relationship of a country with other countries. Pakistan also has relationship with other countries in terms of international trade throughout different years. Conducted study focus on international trade impact on economic growth in Pakistan. For this purpose, yearly data set is taken from period of 1972 to 2012. ARDL regression analysis is used to deal with see the long run and short run relationship among the effect of worldwide exchange on financial development of Pakistan. Descriptive statistics, KPSS unit root test and VIF are obtained for analysis purpose. Eview software is used to obtain results in analysis. The finding of this examination shows that outside direct speculation, genuine successful worldwide rate and urbanization have huge and negative effect on financial development. As worldwide exchange is arrangement instrument may have more impacts in future to the impact on exchange aggressiveness